Optimal Portfolio Analysis of LQ-45 Stocks Based on Capital Asset Pricing Model - Tobing, Ainun Sakinah L; Fitri, Nur Aisyah; Ajmilia, Qori Fadla; Sadalia, Isfenti (West Science Business and Management, 2024)
Analysis of optimal portfolio formation for LQ-45 stocks using the Capital Asset Pricing Model (CAPM) is an interesting and complex topic in financial management. This study aims to calculate the expected return and systematic risk of each LQ-45 stock, and evaluate the combination of these stocks to form an optimal portfolio. By using CAPM and Modern Portfolio Theory (MPT), this study can provide a comprehensive framework to understand the risk-return dynamics of stock investment. Despite the limitations of CAPM, this study shows that CAPM remains an important tool in investment analysis. Recommendations for future research are to conduct further empirical analysis to test the effectiveness of CAPM in various market conditions and develop models that combine CAPM with additional factors to improve return prediction.